Ethnomedicinal survey of medicinal plants used to treat diabetes in Bangi, Selangor, Malaysia - Ahmed, Qamar Uddin; OR, Fatimah; Mat So'ad, Siti Zaiton; Jamal, Parveen (Universiti Putra Malaysia, 2017)
Objectives: Synthetic antidiabetic drugs have been reported to exhibit deleterious effects and have failed to alter the course of diabetic complications. Traditional medicinal plants possessing antidiabetic effects can be a valuable source for the development of safer oral hypoglycemic agents. Hence, the aim of this ethnomedicinal survey was to document the ethno-medicinal plants used for the treatment of diabetes in Bangi, Selangor, Malaysia. Design and methods: The field survey was performed from November 2013 through December 2014. Face-to-face interview and questionnaires were used to assemble information regarding the participants, local name of the plant, origin, parts used and method of herbal remedy. Citation index (CI) for each species mentioned and relative citation index (RCI) were calculated. Results: Thirty species belonging to twenty five families and twenty nine genera were recorded. 63.3% of these species were native while 36.7% were cultivated. The most frequently used part was leaves. Decoction was the most common herbal preparation. Hibiscus rosa sinensis has the highest citation index (CI) followed by Psidium guajava and Cymbopogon citratus with 0.09, 0.08, and 0.07, respectively. Three plants viz. Polyalthia bullata, Rourea concolor and Smilax myosotiflora have never been scientifically validated for their traditional use as antidiabetic agents. Plant species for diabetes treatment varied in every village due to the differences in rate of industrialization, urbanization and environmental degradation. Conclusion: This survey has successfully recognized the plants most commonly used by local practitioners in Bangi community to treat diabetes. Research studies on P. bullata, R. concolor and S. myosotiflora might furnish a new class of safe antidiabetic agents. Keywords: Diabetes, Ethno-medicinal plants, Citation index, Bangi, Malaysia